Market-based monetary policy uncertainty - Michael D. Bauer; Aeimit Lakdawala; Philippe Mueller (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper investigates the role of monetary policy uncertainty for the transmission of FOMC actions to financial markets using a novel model-free measure of uncertainty based on derivative prices. We document a systematic pattern in monetary policy uncertainty over the course of the FOMC meeting cycle: On FOMC announcement days uncertainty tends to decline substantially, indicating the resolution of policy uncertainty. This decline is then reversed over the first two weeks of the intermeeting FOMC cycle. Both the level and the changes in uncertainty play an important role for the transmission of monetary policy to financial markets. First, changes in uncertainty have substantial effects on a variety of asset prices that are distinct from the effects of the conventional policy surprise measure. For example, the Fed's forward guidance announcements affected asset prices not only by adjusting the expected policy path but also by changing market-perceived uncertainty about this path. Second, at high levels of uncertainty a monetary policy surprise has only modest effects on assets, whereas with low uncertainty the impact is significantly more pronounced.
Keywords: E43; E44; E47; 330